SERVIÇOS ECOSSISTÊMICOS E QUALIDADE DE FRAGMENTOS FLORESTAIS URBANOS - JÉSSICA THALHEIMER DE AGUIAR (2021)
Considering the expansion of urban areas, an understanding of how ecological processes work in these areas has become necessary for the maintenance of ecological diversity. Therefore, the objective of this study was to evaluate the quality of urban forest fragments in the city of Irati, Paraná, and the capacity to offer ecosystem services compared to a rural fragment in a federal protected area (FLONA). For this, an area of 1.0 ha was considered for each fragment, given the maximum area of one of the urban fragments. In these places, the following evaluations were carried out: Floristic survey of the adult and regenerating strata of the tree component, spatial distribution of the most abundant species, evaluation of the seed bank and seed rain, rainwater intercept capacity and carbon stock. In the floristic survey (50 plots of 10.0 x 20.0 m), considering all individuals with DBH ≥ 10 cm, the variables DBH, total height and species identification were measured. For the spatial distribution of the species, metric coordinates of location were taken in the plot of all individuals in relation to the X and Y axes. The survey of regeneration was carried out in plots of 1.0 x 20.0 m considering individuals of class 1 ( up to 1 m in height), class 2 (1-3 m) and class 3 (>3 m and DBH ≤ 5 cm). In each regeneration plot the seed bank (seasonally) and seed rain (monthly) were evaluated. Nine rain gauges were installed in each fragment, distributed outside, on the edge and in the center of each study area in order to assess the rainwater interception capacity, the evaluations were carried out monthly in the middle of each season of the year. The carbon stock was estimated for the three areas using different models estimated by Chave, Ratuchne and Martins. A proportion was made between the environmental variables and from this calculated the forest quality and the correlation of these variables with the quality in order to generate a statistical model from the correlated variables in order to determine the environmental quality of an urban forest fragment. In general, the urban green area presented floristic simplification, that is, lower diversity indices when compared to a conserved environment, even so, it was possible to evidence its environmental benefits from the analyzed ecosystem services. In addition, it was possible to generate a model that allows evaluating the environmental quality of the urban green area from environmental variables that are considered important for all types of green areas. The use of the generated model will be extremely important and necessary, taking into account the scarcity of studies on urban green areas and also considering their numerous benefits.